2023
DOI: 10.3390/electronics12071555
|View full text |Cite
|
Sign up to set email alerts
|

GaN and SiC Device Characterization by a Dedicated Embedded Measurement System

Abstract: This work proposes a comparison among GaN and SiC device main parameters measured with a dedicated and low-cost embedded system, employing an STM32 microcontroller designed to the purpose. The system has the advantage to avoid the use of expensive laboratory measurement equipment to test the devices, allowing to obtain their behavior in operating conditions. The following KPIs (Key Performance Indicators) are measured and critically compared: threshold voltage, on-resistance and input capacitance. All the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In [1], Vella et al compare the main parameters of GaN and SiC devices, measured with a dedicated and low-cost embedded system. It is shown that GaN devices achieve higher efficiency with respect to SiC devices in the considered range of switching frequencies.…”
mentioning
confidence: 99%
“…In [1], Vella et al compare the main parameters of GaN and SiC devices, measured with a dedicated and low-cost embedded system. It is shown that GaN devices achieve higher efficiency with respect to SiC devices in the considered range of switching frequencies.…”
mentioning
confidence: 99%